Effects of Aqueous Extracts of Caryocar brasiliense in Mice - Fonseca, Leydiana Duarte; Bastos, Gabriela Almeida; Morais Soares Costa, Marco Aurelio [UNESP]; Paiva Ferreira, Adriano Vinicius de; Franca Silva, Maria Luiza; Vieira, Thallyta Maria; Morais-Costa, Franciellen; Faria de Oliveira, Neide Judith; Duarte, Eduardo Robson (Univ Fed Rio Grande Do Sul, 2016)
Background: Caryocar brasiliense Cambess (Caryocaraceae) is an arboreal plant native of Brasilian Cerrado and its fruit is an important source of food and income for the human population of this region. In addition to using as food, different parts of this tree have great medicinal potential as antimicrobial, anti-inflammatory, antioxidant and antihelmintic. However, the active metabolites those are likely to confer these pharmacological properties healing may also be toxic dependent upon the dose and route of administration. In this quest, the aim of this study was to assess the acute toxicity of aqueous extracts of fruit peels and leaves of C. brasiliense in mice of both genders. Materials, Methods & Results: The aqueous extracts were obtained by decoction, diluted in water and filtered through membrane. The toxicity of extract of fruit peels (62.5 at 500 mg/kg of body weight (BW) and leaf extract (18.75 mg/kg bw) were evaluated in males and females mice (Mus musculus) Swiss by intraperitoneal route. For 2 control groups were administered injection water. The clinical signs and deaths were recorded up to 14 days after administration. The lethal doses for 10 (LD10) or 50 (LD50) % of population were estimated with Probit regression analysis. The Chi-square test was used to analyze differences of mortality frequencies between males and females. The groups treated with the two lower doses of both extracts completely abolished the clinical alteration between two and four hours after inoculation. The comportment of control group's animals was normalized immediately after administration of injection water. The higher dose administered in both experiments were lethal for all animals, but the doses 250 mg/kg BW of fruit peels extract and 150 mg/kg of BW of leaves extract caused mortality of 100% just in males. However, in both experiments there were no significant differences between the mortality frequency for groups of male and female, as well the comportment of these animals when these doses were administered. Dose-dependent response was observed to mortality. The LD10 corresponded to 89.6 mg/kg BW and LD50 was 149.8 mg/kg BW for fruit peel extract. For the leaf extract, LD10 and LD50 were 33.35 and 67.01 mg/kg BW, respectively. Discussion: Aqueous extracts of the fruit peels and leaves of C. brasiliense were classified as very toxic since the LD50 ranged from 50 to 500 mg / kg BW. For both extracts, similar behavioral changes were observed. Among the secondary metabolites present in fruit peel and leaves, saponins and tannins can promote nervous symptoms. Although there are no records in the literature about animals and human orally intoxicated with any part of C. brasiliense, the development of specific studies to determine its toxicity is relevant, considering the social and ecological importance of this plant.
Keywords: Caryocar brasiliense; Mus musculus; Cerrado; intraperitoneal route; toxicidade